Impact of Cloud-based Infrastructure on Telecom Managed Services Models - Anicho, Ogbonnaya; Tariq Abdullah (Data Science: Journal of Computing and Applied Informatics, 2020)
This paper examines how cloud-based infrastructure is impacting classical implementations of telecom Managed Services (MS) models with focus on network operations and maintenance (O&M). The migration of legacy network assets to the ‘cloud’ has altered traditional telecom network configuration. This work explores how cloud-based network infrastructure may alter MS models in the telecom network domain. It is expected that the unique offerings of cloud-based solutions will impact existing MS models and may require redesigning or adjusting operation and maintenance processes and frameworks. As network infrastructure migrates to the cloud, telecom MS delivery models must evolve as well to satisfy new requirements. This paper lays out essential aspects of traditional MS models that may be impacted as a result of cloud-based infrastructure. It further proposes a framework, and conceptual software design for systematically analysing the gaps in current MS models in order to identify requirements for improved MS delivery in the cloud era.